Robotic resection of isolated ovarian cancer recurrence in the lesser sac - Jessica D. St. Laurent; Jason N. Silberman; Michael J. Worley Jr (Elsevier, 2022)
In recurrent ovarian cancer patients the addition of surgical cytoreduction is associated with prolonged overall survival compared to chemotherapy treatment alone when complete cytoreduction is achieved (Harter et al., 2021; Shi et al., 2021; Coleman et al., 2019). In the appropriate surgical candidates, a minimally invasive approach may be used to achieve complete cytoreduction of isolated lesions with proper exposure and surgical planning.This video demonstrates safe robotic entry into the lesser sac and resection of recurrent high-grade serous ovarian carcinoma near the pancreatic neck. The patient is a 78-year-old BRCA negative female with a history of a stage IIIC high-grade serous carcinoma. She previously underwent cytoreductive surgery and adjuvant chemotherapy in 2018 and presented 24 months later with a normal CA 125 and CT findings of an isolated lesion near the porta hepatis. An MRI was obtained preoperatively to further characterize the location of the lesion demonstrating a 2.2 × 1.6 cm hypoechoic mass adjacent to the pancreatic neck. Given the patient's prolonged disease-free interval, fitness for surgery and single site of disease, she met strict inclusion criteria for recent studies demonstrating clinical benefit with secondary cytoreduction (Harter et al., 2021; Shi et al., 2021). She was taken for a robotic secondary cytoreduction. At subsequent follow up 7 months later, our patient was still disease free and continues surveillance. In this video, we demonstrate the careful dissection of this isolated lesion from the omental bursa. We review important pre-procedural and anatomic considerations for robotic surgery in the lesser sac.